New Generalizations of Set Valued Interpolative Hardy-Rogers Type Contractions in b-Metric Spaces - Muhammad Usman Ali; Hassen Aydi; Monairah Alansari (Journal of Function Spaces)
Debnath and De La Sen introduced the notion of set valued interpolative Hardy-Rogers type contraction mappings on b-metric spaces and proved that on a complete b-metric space, whose all closed and bounded subsets are compact, the set valued interpolative Hardy-Rogers type contraction mapping has a fixed point. This article presents generalizations of above results by omitting the assumption that all closed and bounded subsets are compact.